ANALISA KERENTANAN PADA VULNERABLE DOCKER MENGGUNAKAN SCANNER OPENVAS DAN DOCKER SCAN DENGAN ACUAN STANDAR NIST 800-115 - Tika Astriani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Docker is an opensource-based application that allows to build, distribute and runapplications anywhere for developers and docker is also used as a standard container-basedtools. Efforts in measuring a vulnerability in the application can be done by scanning, this effortis useful to find a risk of vulnerability so that it can get the right stategi to shrink or eliminate therisk. In this final task, a vulnerability analysis on docker was performed using an open sourcevulnerability scanner with a reference to the NIST 800-115 standard. This study uses OpenVASas Vulnerability Scanner which has a fairly complete database of vulnerabilities as well asscanning results that are easy to understand. In this analysis, can be detected and analyzedvarious attacks that can be done by attackers in carrying out attacks. Obtained 98.6 from the riskanalysis profile and shows that WordPress User IDs and User Names Disclosure have thegreatest risk of cyber attacks.Keywords— Docker,NIST,OpenVAS,Vulnerability